2010
DOI: 10.1152/ajplung.00415.2009
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular acidification stimulates IL-6 production and Ca2+mobilization through proton-sensing OGR1 receptors in human airway smooth muscle cells

Abstract: . Extracellular acidification stimulates IL-6 production and Ca 2ϩ mobilization through proton-sensing OGR1 receptors in human airway smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 55 publications
6
84
1
Order By: Relevance
“…Ichimonji et al demonstrated in human airway smooth muscle cells that GPR68 mediated extracellular acidification-induced production of pro-inflammatory cytokine IL-6 and increased intracellular Ca 2+ concentration. 64 The same group also found that extracellular acidification of pH 6.3 induced the expression of CTGF, which was involved in the formation of extracellular matrix proteins and associated with airway remodeling, through the GPR68/G q/11 /IP 3 /Ca 2+ pathway. 65 Furthermore, Saxena et al demonstrated that GPR68 receptor mediated airway smooth muscle cell contraction in an acidic extracellular environment.…”
Section: Role For the Ph-sensing Gpcrs In The Respiratory Systemmentioning
confidence: 93%
See 1 more Smart Citation
“…Ichimonji et al demonstrated in human airway smooth muscle cells that GPR68 mediated extracellular acidification-induced production of pro-inflammatory cytokine IL-6 and increased intracellular Ca 2+ concentration. 64 The same group also found that extracellular acidification of pH 6.3 induced the expression of CTGF, which was involved in the formation of extracellular matrix proteins and associated with airway remodeling, through the GPR68/G q/11 /IP 3 /Ca 2+ pathway. 65 Furthermore, Saxena et al demonstrated that GPR68 receptor mediated airway smooth muscle cell contraction in an acidic extracellular environment.…”
Section: Role For the Ph-sensing Gpcrs In The Respiratory Systemmentioning
confidence: 93%
“…31 N/A Regulates gene expression and airway smooth muscle cell contraction. [64][65][66][67] GPR68-null mice are resistant to asthma. 68 Skeletal inhibits osteoclastic bone resorption; relative bone density is reduced in GPR65-null mice.…”
Section: Respiratorymentioning
confidence: 99%
“…TDAG8, as well as GPR4, exhibited transforming activities when ectopically overexpressed in immortalized cell lines (Sin et al, 2004). Furthermore, the proton-sensing GPCRs have been shown to regulate immune cell function and inflammatory responses (Ichimonji et al, 2010;Mogi et al, 2009;Onozawa et al, 2011). These observations suggest that the proton-sensing GPCRs may represent novel targets for cancer treatment, inflammation inhibition, and chemoprevention.…”
Section: Molecular Targeting Of Acidosis-related Pathwaysmentioning
confidence: 97%
“…In fact, OGR1 has been reported to be involved in a variety of physiologically important responses to extracellular acidification using a knockdown strategy of the receptor in several types of cells in vitro, e.g., receptor activator of nuclear factor-κB ligand (RANKL)-induced differentiation in osteoclasts [42], Ca 2+ mobilization, cyclooxygenase (COX)-2 induction, and prostaglandin synthesis in osteoblasts [43,44] and vascular smooth muscle cells [45,46], and IL-6 and connective tissue growth factor production in airway smooth muscle cells [47][48][49]. Similarly, TDAG8 has been shown to mediate acidic pH-induced inhibition of apoptosis in eosinophils [50], inflammatory cytokine production in macrophages [51], and O 2 -production in neutrophils [52].…”
Section: In Vitro Analysis Of Insulin Secretionmentioning
confidence: 99%
“…Most of previous studies on the role of OGR1 were observed at pathophysiological acidic pH of less than pH 7.0 [39]. For example, COX-2 expression and PGE 2 production in osteoclasts [43] and IL-6 and connective tissue growth factor (CTGF) production in airway smooth muscle cells [47,48] in response to acidic pH are observed at pH 6.8 to 6.3. The activation of OGR1 at neutral pH 7.4, however, is not unusual because a remarkable activation of OGR1 at pH 7.4 is observed in CHO cells and in HEK293 cells, in which OGR1 expression was forced [19,62].…”
Section: In Vivo Analysismentioning
confidence: 99%